Acontribution to study chemical constituents of Desmodium gangeticum of Viet Nam - Ha, Le Minh; Phuong, Ngo Thi; Huyen, Do Thi Thanh; Ngoc, Duong Bich; Viet, Nguyen Minh; Anh, Nguyen Tuan; Dat, Nguyen Tien; Long, Pham Quoc (Vietnam Journal of Science and Technology, 2019)
From the ethyl acetate extract of the leaves of Desmodium gangeticum collected in Me Linh, Ha Noi, we isolated 5 compounds including luteolin (1), luteolin tetramethyl ether (2),  N,N-dimethyl tetradecane-1-amin (3), D-pinitol (4)  and stigmasterol (5). In which, luteolin (1) was isolated from Desmodium gangeticum for the first time, luteolin tetramethyl ether (2) and  N,N-dimethyl tetradecane-1-amin (3) were first isolated from genus Desmodium. Their structures were determined by 1D and 2D NMR spectra.